O alinhamento estratégico da tecnologia de informação na Universidade Federal do Ceará - Rodrigues, Sandra Maria Coelho (2009)
In the strategic management of Higher Education Institutions (HEIs), the Information Technology (IT) is a fundamental aspect whose effective application requires alignment with business strategies. The aim of this work is mainly to describe the alignment process of Information Technology and business areas in HEIs based on the application of the model developed by Jerry Luftman - SAMM (Strategic Alignment Maturity Model). The conceptual model was developed from a review of the literature on the subject of alignment with IT and business strategies and in particular, those related to strategic management in HEIs. We opted for an investigation combining quantitative and qualitative aspects in a descriptive exploratory case study at the Federal University of Ceará (UFC). To collect the primary data, we developed an electronic questionnaire, which was answered by 82 university administrators, namely: pro-rectors, engineers, principals, superintendents and heads of academic units. The results obtained, not only allowed the identification of a low level of maturity concerning the alignment with the IT and business strategies of the UFC but they also made possible the analysis of the factors that affect the process, especially as regards such facilitating and inhibiting practices. The research highlights the need to direct the attention of managers to some of these factors which can be translated into opportunities for the improvement of the process.